Water flow risks and stakeholder impacts on the choice of a dam site - Biçak, HA; Jenkins, GP; Özdemirag, A (Blackwell Publ Ltd, 2002)
This study evaluates three alternative locations for building a fresh water dam in the Yesilirmak Valley of North Cyprus. Each of the three sites has different investment costs, water storage capabilities and socio-political repercussions. These kinds of tradeoffs have in recent years characterised much of the worldwide debate surrounding the construction of electricity and irrigation dams. Another issue raised in this paper is the appropriate treatment of the risk and variability associated with the availability of water to fill the dam through time. This paper demonstrates how an integrated financial-economic-stakeholder analysis can provide the inputs needed by decisionmakers in such situations to make rational political and economic choices.